PEMBENTUKAN KARAKTER ANAK SEKOLAH MINGGU MELALUI PEMBELAJARAN CERITA ALKITAB DI HKBP TAPIAN NAULI RESORT LUMBAN LOBU DISTRIK IV TOBA - Shinta Tampubolon; Hersakso Sinurat; Yetti Lubis; Zesi Panjaitan (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2026)
This community service program aimed to strengthen the character of Sunday School children through Bible storytelling at HKBP Tapian Nauli Resort Lumban Lobu. The activity involved 30 children aged 6–12 years and was conducted in three meetings using a participatory educational approach. Program stages included ice breaking, singing, prayer, Bible reading, storytelling sessions, question-and-answer discussions, reflective games, and group activities. Data were collected through participatory observation and simple evaluation sheets focusing on participation, comprehension of moral messages, and character-related behavior. The results showed that 83% of participants were able to retell Bible stories correctly, 80% demonstrated improved understanding of moral values, and 78% showed positive behavioral indicators such as obedience, cooperation, respect for parents, courage, and empathy. In addition, children’s learning enthusiasm and participation increased during interactive sessions supported by visual media and educational games. This program indicates that Bible storytelling is an effective and contextual pedagogical strategy for strengthening children’s moral and spiritual character in church-based learning environments.